Food Estate Program Law Politics - Ditta Wisnu (Journal of Contemporary Sociological Issues, 2022)
This study aims to determine the implications of the food estate program on the fulfillment of the rights of the Dayak people of Central Kalimantan and the legal policy of the preparation and implementation of the National Economic Recovery Program (NERP) through the Food Estate in Central Kalimantan in line with the principles of human rights and traditional values of the Central Kalimantan Dayak. The type of research used in compiling this research is empirical normative juridical research. This research is descriptive. The types of data used are primary data and secondary data. Primary data collection techniques through interviews while secondary data obtained through library research. Primary and secondary data were analyzed qualitatively. The results of the study show that: First, the Food Estate Program in Central Kalimantan, which is one of the national economic recovery programs (NERP) has had a significant impact on the indigenous Dayak people of Central Kalimantan who have ties to forests, land and rivers as well as causing vertical and horizontal conflicts in their lives’ implementation. Second: the Central Government and Local Governments in formulating regulations and policies, on the one hand, have the enthusiasm to pay attention to the customary values and traditions of the Dayak indigenous people of Central Kalimantan but are weak at the implementation stage, causing conflicts due to the issuance of Law of the Republic of Indonesia No. 11 of 2020 concerning Job Creation and its derivative regulations that put forward the principle of omnibus law which aims to create a quality business and investment climate without paying attention to the principles of human rights, ecological justice and the customary values and traditions of the Dayak people of Central Kalimantan. Keywords: Legal policy, Human Rights, Ecological Justice.